Association between Maternal Hemoglobin Level and Incomplete Abortion in A West Java Tertiary Hospital, Indonesia - Anabela, Lisa Milena; Handono, Budi; Prihatni, Delita; Aziz, Muhammad Alamsyah; Ritonga, Mulyanusa Amrullah (International Journal of Integrated Health Sciences, 2023)
Objective: To evaluate the association between maternal hemoglobin concentrations and incomplete abortion.Methods: An analytic, cross-sectional study with consecutive sampling method was conducted using medical records of 45 pregnant women aged 18 – 35 years old visiting the Obstetrics and Gynecology Department of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia from January 1, 2017 to December 31, 2019. Participants were grouped into incomplete abortion and non-abortion groups.Results: Maternal characteristics in the incomplete abortion group showed that the majority of pregnant women in this group were 25.58 years of age, non-anemic (n=37, 82.22%), had no previous spontaneous abortion (n=40, 88.89%), and were nulliparous (n=25, 55.55%) with a mean interpregnancy interval of 4.03 years. The characteristics in both incomplete abortion group and non-abortion group were homogenous in the level of anemia (p-value=0.380), previous spontaneous abortion (p-value=1.00), and interpregnancy intervals (p-value=0.667). The mean hemoglobin concentration for the incomplete abortion group was 11.81 gr/dL (95% CI, 11.30 to 12.26). Heterogenous data was found in age (p-value=<0.001) and parity (p-value=0.002). Parity was a strong confounder, causing the hemoglobin concentration insignificantly associated to incomplete abortion (p-value=0.884).Conclusion: No statistically significant association is found between hemoglobin concentration and incomplete abortion. Most women with incomplete abortion are around 25 years old, nulliparous, non-anemic with a mean hemoglobin concentration of 11.81 gr/dL with no history of previous abortion, and a rather secure interpregnancy intervals.